Facile fabrication of polyethylene/silver nanoparticle nanocomposites with silver nanoparticles traps and holds early antibacterial effect - Anh D. (2017)
© 2016 Wiley Periodicals, Inc. Antibacterial polyethylene (PE)/silver nanoparticle (AgNP) nanocomposites containing AgNPs at concentrations of 5 × 10 -5 , 5 × 10 -4 , and 5 × 10 -3 wt % were fabricated and tested. Transmission electron microscopy revealed an even dispersion of surface AgNPs in the PE/AgNP nanocomposites. No AgNP agglomeration was observed. The tensile strength, elongation at break, and Young's modulus of these PE/AgNP nanocomposites were similar to those of neat PE. Differential scanning calorimetry demonstrated that the PE/AgNP nanocomposites and neat PE had similar melting and crystallization temperatures of 126 ± 0.5 and 109 ± 0.6C, respectively. The heats of fusion of the PE/AgNP nanocomposites containing AgNPs at concentrations of 5 × 10 -5 and 5 × 10 -4 and of 5 × 10 -3 wt % were lower than those of neat PE by 5 and 7%, respectively. These PE/AgNP nanocomposites were immersed in shaking liquid cultures of the potential pathogenic bacteria Escherichia coli, Bacillus subtilis, and Salmonella typhimurium in the lag phase. The results show that the growth rates of all of the tested bacteria were restricted effectively after 1.5, 3, and 6 h of cultivation, respectively.